2021
DOI: 10.25304/rlt.v29.2383
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the attention, relevance, confidence and satisfaction (ARCS) of students through interactive science learning multimedia

Abstract: The use of interactive multimedia has the potential to create a high-quality learning environment. The key elements of various media, user control over information delivery and interactivity can be used to improve the learning process by creating an integrated learning environment. This study aims to determine the increase in students’ attention, relevance, confidence and satisfaction (ARCS) before and after using interactive science learning multimedia. This study collected data from 30 students aged 12–13 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…On the other hand, studies related to the ARCS motivational design such as those of Turel & Ozer Sanal (2018) determine that the use of a digital learning material based on Keller's model helps to improve academic performance and motivation level showing a significant difference in the experimental and control group of 1100.487, p<,01; on the other hand Khan et al (2019) showed the increase of students' learning motivation after using augmented reality mobile application also determined that attention, confidence and satisfaction increased based on the percentage differences while the relevance factor decreased, coinciding with the positive result of using ARCS motivational model, on the other hand Hsu (2020) showed in his quasi-experimental study that learning motivation through virtual reality improved by 7.30 in all aspects where it increased 0.25 in "Attention", 0.16 in "Relevance", 0.16 in "Confidence" and 0.34 in "Satisfaction". On the other hand Herianto & Wilujeng (2021) indicates that the use of interactive multimedia learning can significantly improve students' learning motivation, particularly attention which increased by 10.83%, confidence with an increase of 13.60%, and satisfaction with an increase of 9.54%; however, the relevance aspect of students' learning motivation did not increase significantly as it only increased by 1.45%.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, studies related to the ARCS motivational design such as those of Turel & Ozer Sanal (2018) determine that the use of a digital learning material based on Keller's model helps to improve academic performance and motivation level showing a significant difference in the experimental and control group of 1100.487, p<,01; on the other hand Khan et al (2019) showed the increase of students' learning motivation after using augmented reality mobile application also determined that attention, confidence and satisfaction increased based on the percentage differences while the relevance factor decreased, coinciding with the positive result of using ARCS motivational model, on the other hand Hsu (2020) showed in his quasi-experimental study that learning motivation through virtual reality improved by 7.30 in all aspects where it increased 0.25 in "Attention", 0.16 in "Relevance", 0.16 in "Confidence" and 0.34 in "Satisfaction". On the other hand Herianto & Wilujeng (2021) indicates that the use of interactive multimedia learning can significantly improve students' learning motivation, particularly attention which increased by 10.83%, confidence with an increase of 13.60%, and satisfaction with an increase of 9.54%; however, the relevance aspect of students' learning motivation did not increase significantly as it only increased by 1.45%.…”
Section: Introductionmentioning
confidence: 86%
“…▪ Confidence: This is linked to students' expectations of achievement and success that drive a continued desire to learn by feeling satisfied with the outcomes of a learning experience (Herianto & Wilujeng, 2021). Learners must understand and have the impression that they will achieve the purpose of a learning activity by understanding the sources of information, materials, and tools they use, which will build their confidence to achieve the development of evidence.…”
Section: Socrative Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Fun in learning, interest in learning time, social implications, scientific normality for science learning (Sulistioning et al, 2020), & outdoor learning (Skarstein & Ugelstad, 2020) Learning should not only be in classroom 8 Necessity of media literacy (Anwar et al, 2020) that is embodied in the form of science learning framework online (Opere, 2021), online community (Herodotou et al, 2022), flipped classroom (Shana & Alwaely, 2021), open educational resources (Gerard et al, 2022), use of multimedia (Herianto & Wilujeng, 2021), virtual reality understanding (Hite, 2022), virtual science learning (Telenius et al, 2020), using Edmodo (Ryane & El Faddouli, 2020), animated videos (Nurhayati et al, 2022), motion graphic animation videos (Hanif, 2020), mobile science learning (Chang et al, 2021;Jeno et al, 2020)., VR simulations (Pande et al, 2021) Science learning media must be technologically advanced 9 10 Urgency of cognitive assessment techniques (Darmawan et al, 2020), multiple self-regulated learning measures (Gandomkar et al, 2020), & performance assessment (Yakob et al, 2021).…”
Section: Science Learning Needsmentioning
confidence: 99%
“…The implementation of technology, especially interactive media, can result in an increase in students' satisfaction. In Herianto and Wilujeng's study, they examined the impact of interactive multi-media for science education on students' satisfaction, relevance, attentiveness, and confidence [26]. It is found that the use of interactive multi-media increases students' satisfaction for learning, with strong positive feedback on students' satisfaction.…”
Section: Learning Outcomes As Seen From Student Satisfactionmentioning
confidence: 99%